Financial analysis of Serbian companies undergoing privatization - Vesković, Nino (The European Journal of Applied Economics, 2016)
This study presents a financial analysis of companies undergoing the process of privatization in the Republic of Serbia (RS). A total of 182 of such companies were examined and compared to an equal number of randomly chosen companies of comparable size. The results revealed a significant gap between the financial performances of the two samples. For that reason, the companies undergoing privatization need to undergo radical changes for the purpose of achieving a higher level of profitability and preventing further losses. Given that these companies pose a significant challenge for the Serbian economy, the author believes that this study will serve as a reference for further research. In addition, this manuscript shall present the comparative analysis of the total net loss of the observed companies and the gross domestic product of the RS, as well as between the corresponding number of employees for the year 2013.
Keywords: financial statement analysis; Z-score model; liquidity; debt; profitability; privatization